PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR PADA MATERI KERAJAAN KELAS IV DI SDN KEPATIHAN - Atikah Riswandani; Titi Anjarini; Suyoto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to: (1) determine the implementation of the Mind Mapping method in the topic of kingdoms in Grade IV at SDN Kepatihan; (2) determine the improvement of students' learning motivation in the topic of kingdoms in Grade IV at SDN Kepatihan; and (3) determine the improvement of students' learning outcomes in the topic of kingdoms in Grade IV at SDN Kepatihan.This research is a Classroom Action Research. The core concept of action research according to Lewin consists of planning, action, observation, and reflection. The study was conducted in two cycles involving 28 students. The data collection techniques used were qualitative (in the form of observation of learning implementation) and quantitative, including: (1) the percentage of learning implementation using the mind mapping method, (2) the percentage of learning motivation using a questionnaire, and (3) improvement in learning outcomes obtained through tests in each cycle.The results of this study show that: (1) The implementation of the mind mapping method was successful, with an average percentage of 70% (good category) in Cycle I and 85% (very good category) in Cycle II; (2) Students’ learning motivation in the IPAS subject on the topic of kingdoms increased from an average of 67.09% (good category) in Cycle I to 79.01% (good category) in Cycle II; (3) Students’ learning outcomes increased from an average score of 59.28 (fair category) in Cycle I to 79.45 (good category) in Cycle II. It can be concluded that the mind mapping method can improve students’ motivation and learning outcomes.